EKSPEKTASI RASIONAL: PAST, PRESENT AND FUTURE - Helmi Noviar (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2016)
This article discusses the rational expectations theory in the perspective of the appearance process and its contribution to economic thought in terms of the science and its application on the economy. The methodology in writing this paper is through literature review, generally taken from journal articles which examine from two viewpoints: from economists who initiated and supported the concept of this theory and those who opposed it. Furthermore, it also discuss about its application, particularly in terms of future economic studies. As part of the New Classical Economics, the theory pioneered by Robert E. Lucas, Jr. along with Thomas J. Sargent has provided a great contribution of empirical and multifaceted approaches, which provides a compilation of the results of the study and generalization theory by numerous macroeconomist and econometrician in Rational Expectations and Econometric Practice (1981), it quite influential on level of academic and applied economics. In other words, the rational expectation revolution is one of the important components in modern economic theory, the New Classical Economics and New Keynesian Economics.Artikel ini membahas teori ekspektasi rasional dalam perspektif proses munculnya teori ini dan kontribusinya terhadap paham pemikiran ekonomi baik dari sisi ilmu pengetahuan maupun aplikasinya dalam suatu perekonomian. Metodologi penulisan artikel ini melalui review literatur dari sumber jurnal dengan memisahkan dua sudut pandang terhadap teori rasional ekspektasi: dari sisi ekonom yang menggagas dan mendukung konsep teori ini dan yang bertentangan. Selanjutnya, dalam artikel ini juga membahas aplikasi teori ini dalam studi-studi ekonomi di masa mendatang. Sebagai bagian dari paham ekonomi klasik baru, teori yang diinisiasi oleh Robert E. Lucas, Jr. bersamaThomas J. Sargent melahirkan karya kumpulan artikel dari beberapa ahli ekonomi makro dan ekonometrika dalam Rational Expectations and Econometric Practice (1981) yang cukup berpengaruh pada tataran akademis dan aplikasi ilmu ekonomi. Dengan perkataan lain, revolusi ekspektasi rasional, merupakan salah satu komponen penting dalam teori ekonomi modern seperti halnya paham Ekonomi Keynesian baru dan Ekonomi klasik baru.